Frequency of oral cancer in Babol during 2012-2016 - Azade Mahmuodi Kelarijani; Mohamad Mehdi Naghibi Sistsni; Shima Nafarzade (Babol University of Medical Sciences, 2019)
Introduction: Regarding the lack of data on the  frequency of oral cancer in Babol, the aim of this study was to evaluate the frequency of oral cancer in Babol during 2012-2016. Material & Methods: This retrospective cross-sectional study was performed using pathology sheet records of oral cancer patients during 2012-2016. Survival status of patients was collected through telephone contact. Results: The mean age of 48 patients was 62.2% (22-95) years, and 64.2% were male. Squamous cell carcinoma (SCC) was the most prevalent malignancy, and the most common site was tongue followed by pharynx. Frequency of oral cancer patients was 9 (18.8%), 9 (18.8%), 10 (20.8%), 12 (25%) and 8 (16.7%) patients from 2012 to 2016, respectively. Conclusion: SCC, specifically on the tongue was the most frequent malignancy. It seems that the oral cancer prevention training is necessary for elderly adults.